MODERN METHODS AND CRITERIA FOR ASSESSING TEACHERS’ PROFESSIONAL COMPETENCIES IN VOCATIONAL EDUCATION INSTITUTIONS - Javohir Otayarov (Web of Journals Publishing, 2025)
This article analyzes contemporary approaches and criteria for assessing the professional competencies of teaching staff. The concept of professional competence and the necessity of its assessment are explained, and, based on recent scholarly sources, studies on methods for assessing teachers’ professional competence are reviewed. The article presents the results of a survey conducted among 100 teachers, including a table of average scores for various areas of professional competence. Statistical analysis revealed differences across age groups (for example, teachers over 55 scored higher in digital and innovation competencies). The findings are compared with the scholarly literature, and the importance of modern assessment criteria — including predefined competency standards, authentic assessment (tasks in real contexts), portfolios, and multisource (360-degree) feedback — is discussed. It is emphasized that assessment processes must be organized using impartial, reliable, and up-to-date methods to ensure teachers’ professional development.
Keywords: Pedagogical competence, competency-based assessment, 360-degree assessment, portfolio assessment, authentic assessment, digital competence, innovation competence, leadership and research competencies, competency standards, professional competencies, assessment criteria.